The Amoskeag Manufacturing Company - Sweezy, Alan R. (Quarterly Journal of Economics, 1938)
Introduction, 473. — I. Prosperity, 474. — Financial ties, 474. — Accounting practices, 478. — Control, 481. — II. Transition, 484. — Facing depression, 486. — Plan adopted: first step, 489; second step, 492. — III. The Decline; financial, 497; physical, 501; the employees and the community, 504. — IV. Liquidation, 507. — The question of responsibility, 511.